2003
DOI: 10.1128/jvi.77.5.3050-3057.2003
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the Human Immunodeficiency Virus Type 1 (HIV-1) env Sequence after Vertical Transmission in Mother-Child Pairs Infected with HIV-1 Subtype A

Abstract: Although several virologic and immunologic factors associated with an increased risk of perinatal human immunodeficiency virus type 1 (HIV-1) transmission have been described, the mechanism of mother-to-child transmission is still unclear. More specifically, the question of whether selective pressures influence the transmission remains unanswered. The aim of this study was to assess the genetic diversity of the transmitted virus after in utero transmission and after peripartum transmission and to compare the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
47
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 31 publications
7
47
0
Order By: Relevance
“…MTCT occurs in utero, during delivery, and through breastfeeding, at a rate of approximately 30% in the absence of antiretroviral therapy (6,19). Previous studies have demonstrated that, despite a complex viral population in the mother, only viruses of a restricted subset were typically transmitted to the infant (1,23,29,40,41,45,48). This suggests that some viruses may be favored for transmission in this setting.…”
mentioning
confidence: 97%
“…MTCT occurs in utero, during delivery, and through breastfeeding, at a rate of approximately 30% in the absence of antiretroviral therapy (6,19). Previous studies have demonstrated that, despite a complex viral population in the mother, only viruses of a restricted subset were typically transmitted to the infant (1,23,29,40,41,45,48). This suggests that some viruses may be favored for transmission in this setting.…”
mentioning
confidence: 97%
“…We also found evidence for the transmission of multiple viral variants in 2 of 10 IUinfected infants and 4 of 9 IP-infected infants, 6 of 19 overall. Previous studies of MTCT, using similar methods, found a heterogeneous infant viral population in 7 of 13 infants infected with subtype CRF01_AE (4 of 6 infected IU and 3 of 7 infected IP) and in 3 of 17 infants infected with subtype A (unknown transmission timing) (47,57). Thus, our data for subtype C HIV-1 transmission are in line with previous studies of other subtypes in the frequency of multiple-variant transmission in MTCT, and overall with the conclusion that in a majority of cases the infant is infected with a single variant.…”
Section: Discussionmentioning
confidence: 99%
“…5 This inefficiency of transmission indicates that anatomical, innate, and/or adaptive mechanisms of protection are able to prevent transmission to a great extent. [6][7][8][9][10][11] Maternal antibodies could prevent infection either through direct binding of virus in the breast milk, or by their systemic and mucosal presence in the infant. This passive maternal immunity in the infant increases in concentration during the last trimester of gestation, and continues to pass into the infant through breastfeeding.…”
mentioning
confidence: 99%